A simple way to prepare a hydrophobic Sr[LiAl3N4]:Eu2+ phosphor with improved moisture resistance. (September 2018) - Zhong, Hao; Wang, Jun-Wei; Dong, Bin-Bin; Li, Lin; Yang, Ming-Ye; Yu, Jun-Ling; Xin, Xu; Agathopoulos, Simeon
Graphical abstract: Highlights: A simple modification method to transform SrLiAl3 N4 :Eu 2+ into hydrophobic phosphor. A thin organosilica layer (about 5–10 nm) was coated on the surface of SLA phosphor. The modified phosphor features superior stability under extremely environment. Abstract: The red-emitting Sr[LiAl3 N4 ]:Eu 2+ (SLA) phosphor was synthesized under flowing N2 gas. A thin organosilica layer (about 5–10 nm) was coated on the surface of SLA phosphors by a very simple method, which transformed the phosphor surface from hydrophilicity to hydrophobicity. The contact angle of water droplets on the surface of the packed SLA phosphors was more than 140°. Compared with the unmodified sample, the modified SLA phosphors could keep at a high emission intensity for more than twice the time under an extremely high moisture level (at relative humidity of 100%, 85 °C). The hydrophobic modification could also improve the uniform dispersion of phosphors during assembly process of white LED.